Korean Wave as the main soft power tool of South Korea - Siemińska, Dorota (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
The Korean Wave is a very important element of South Korea’s soft power and has been bringing a lot of benefits to the country for many years. Over the past decade, it has evolved into a global sensation and gradually the whole world is becoming interested in it. This is a phenomenon worth investigating due to the wide range of aspects in which it applies. Politicians around the world recognize it as a powerful phenomenon and it appears in the speeches of not only the presidents of South Korea, but also foreign presidents in relation to the Korean state. In addition to politics, the Korean Wave also helps to increase the level of the economy and influences social views. The main purpose of this work was to show the impact of the Korean Wave and how the government uses it to build the image of the country. The methodology used to study this topic is mainly qualitative and quantitative data. The author also uses a comparative method, discussing, for example, the views of different countries on the Korean Wave and its impact on mutual relations. The work answers the questions: how the Korean Wave has changed over the past twenty years; how the head of state connects official meetings with Korean culture; how it affects relations with specific countries. The thesis was adopted: The Korean Wave has a positive impact on building the image of the state, and the Korean government has noticed its potential and skilfully uses it. As a result of the analysis of available literature and Internet data, this thesis has been confirmed.